Large Extracellular Vesicle-Associated Rap1 Accumulates in Atherosclerotic Plaques, Correlates With Vascular Risks and Is Involved in Atherosclerosis. Issue 6 (28th August 2020) - Perdomo, Liliana; Vidal-Gómez, Xavier; Soleti, Raffaella; Vergori, Luisa; Duluc, Lucie; Chwastyniak, Maggy; Bisserier, Malik; Le Lay, Soazig; Villard, Alexandre; Simard, Gilles; Meilhac, Olivier; Lezoualc'h, Frank; et al.
Abstract : Rationale: Metabolic syndrome (MetS) is a cluster of interrelated risk factors for cardiovascular diseases and atherosclerosis. Circulating levels of large extracellular vesicles (lEVs), submicrometer-sized vesicles released from plasma membrane, from MetS patients were shown to induce endothelial dysfunction, but their role in early stage of atherosclerosis and on vascular smooth muscle cells (SMC) remain to be fully elucidated. Objective: To determine the mechanisms by which lEVs lead to the progression of atherosclerosis in the setting of MetS. Methods and Results: Proteomic analysis revealed that the small GTPase, Rap1 was overexpressed in lEVs from MetS patients compared with those from non-MetS subjects. Rap1 was in GTP-associated active state in both types of lEVs, and Rap1-lEVs levels correlated with increased cardiovascular risks, including stenosis. MetS-lEVs, but not non-MetS-lEVs, increased Rap1-dependent endothelial cell permeability. MetS-lEVs significantly promoted migration and proliferation of human aortic SMC and increased expression of proinflammatory molecules and activation of ERK (extracellular signal-regulated kinase) 5/p38 pathways. Neutralization of Rap1 by specific antibody or pharmacological inhibition of Rap1 completely prevented the effects of lEVs from MetS patients. High-fat diet-fed ApoE −/− mice displayed an increased expression of Rap1 both in aortas and circulating lEVs. lEVs accumulated in plaque atherosclerotic lesions depending on the progression of atherosclerosis. lEVs from high-fat diet-fed ApoE −/− mice, but not those from mice fed with a standard diet, enhanced SMC proliferation. Human atherosclerotic lesions were enriched in lEVs expressing Rap1. Conclusions: These data demonstrate that Rap1 carried by MetS-lEVs participates in the enhanced SMC proliferation, migration, proinflammatory profile, and activation of ERK5/p38 pathways leading to vascular inflammation and remodeling, and atherosclerosis. These results highlight that Rap1 carried by MetS-lEVs may be a novel determinant of diagnostic value for cardiometabolic risk factors and suggest Rap1 as a promising therapeutic target against the development of atherosclerosis. Abstract : Supplemental Digital Content is available in the text.